2008
DOI: 10.1590/s1516-31802008000200014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for benefits from treating cervical ectopy: literature review

Abstract: CONTEXT AND PURPOSE: Uterine cervical ectopy (cervical erosion) is today considered to be a physiological condition, but there still seems to be a strong tendency towards treating it. The purpose of this study was to review the medical literature for evidence regarding benefits from treating cervical ectopy. METHODS: The following databases were reviewed: Medical Literature Analysis and Retrieval System Online (Medline), Excerpta Medica Database (Embase), Literatura Latino-Americana e do Caribe em Ciências da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 42 publications
(73 reference statements)
1
33
0
1
Order By: Relevance
“…Diagnosis and treatment of cervical glandular ectropion in Poland is very common and relatively costly despite the fact that this lesion is currently regarded as a physiological condition (19). It is also possible that services provided for collection and evaluation of opportunistic Pap smears and diagnostic procedures in CIN cases were erroneously coded with N86 code and therefore overvalued treatment of ectropion in Poland and undervalued costs of opportunistic screening and management of CIN.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis and treatment of cervical glandular ectropion in Poland is very common and relatively costly despite the fact that this lesion is currently regarded as a physiological condition (19). It is also possible that services provided for collection and evaluation of opportunistic Pap smears and diagnostic procedures in CIN cases were erroneously coded with N86 code and therefore overvalued treatment of ectropion in Poland and undervalued costs of opportunistic screening and management of CIN.…”
Section: Discussionmentioning
confidence: 99%
“…This condition has many names in medical terminology: ectropion, erythroplakia, macula rubra and erosion. [1] Cervical ectopy is a condition where the ectocervix contains columnar cells. Squamous cells which cover the cervix are multiple layers thick.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that most women, if not all, will have ectopy at some point during their lifetimes. [1] There are many factors associated with cervical ectopy conditions such as: the use of oral contraceptive pills (OCPs) and intra-uterine contraceptive devices (IUCDs) has been implicated as a cause of cervical ectopy. A prevalence study in China among female users of family planning services reported that 43.2% of women had cervical ectopy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations